Intentionality and communicative tactics of crisis discourse - Pilgun, Elena V. (Journal of the Belarusian State University. Philology, 2019)
The article is devoted to intentionality of crisis discourse. The aim of the article is to detect the main intentions and tactics of crisis discourse on the example of the Russian language articles about migrant and economic crises. Crisis situations often become reasons for a number of communicative episodes among different classes of a society. In modern communicative space many of such crises touch the sphere of international relations; they are to implement political aims and ambitions. The classification of crisis discourse techniques is given. The necessity of such division is grounded, and the examples are provided. The author comes to the conclusion that the intentions of crisis discourse are implemented by means of communicative tactics which are classified according to the main intention characteristics: integration, orientation, disorientation, neutralization, agonality.
Keywords: discourse of crisis situations; communicative tactics; ideologization of public consciousness; intentionality; neutralization; integration; orientation; agonality